(3agQSJ eDdaGJ GdYdGeI LdGd GdOjf GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3UGdM GdMGRe GdQTjOi GdMfai s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdLdGd GdSjhWi GdTGaYi GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai gPg agQSJ eDdaGJi eQJHkG Ydi Gdafhf ai GdJaSjQ hJYdjbGJ GdbQBf GdOQ GdefKhQ ai GdJaSjQ GdeCKhQ s
(3BNQgG (B:s
(3JHjV GdUMjaI ai efGbH GdEeGe CHj MfjaI fRgI GdeeGdc HefGbH GdEeGe eGdc Je hGddg SHMGfg hJYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3Hg eWGdH ddcJGHs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3agGQS hecJHGJs